ChemInform Abstract: Water‐ and Organo‐Dispersible Gold Nanoparticles Supported by Using Ammonium Salts of Hyperbranched Polystyrene: Preparation and Catalysis. Issue 19 (13th May 2014) - Gao, Lei; Nishikata, Takashi; Kojima, Keisuke; Chikama, Katsumi; Nagashima, Hideo
Abstract Gold nanoparticles stabilized by ammonium salts of hyperbranched polystyrene are prepared.